Associations between parental mediation and adolescents' internet addiction: The role of parent–child relationship and adolescents' grades - Li, Xiaojing; Ding, Ying; Bai, Xianchun; Liu, Lisha (Frontiers in Psychology, 2022)
Family factors such as parental mediation on Internet use and parent-child relationships had been shown to play a crucial role in preventing adolescents’ Internet addiction. Previous studies have shown change in characteristics of online risk during adolescents’ development. However, it is still of great interest whether such difference applied in the relationship among parent-child relationship, different types of parental mediation and adolescents’ Internet addiction level. In this study, we investigated the associations between different types of parental mediation and adolescents’ Internet addiction level and how the association was mediated by father- and mother-child relationship. We further investigated whether mediating effect differ between primary and middle school children. Results from a sample of 3026 school children aged 9-14 years (M = 11.56, SD = 0.71; 55.25% primary school adolescents, 44.75% secondary school adolescents) showed that (1) The Internet addiction level and intensity of parental mediation was higher among primary school adolescents than secondary school adolescents. (2) Parental active mediation and monitoring on Internet use was associated with reduced and increased adolescents’ Internet addiction. (3) Father-child relationship had stronger partial mediating effects on the relationships between parental mediation and adolescents’ Internet addiction than mother-child relationship. (4) The relationships among parental mediation, parent-child relationship and Internet addiction were more pronounced among primary school adolescents than secondary school adolescents. These findings suggest that good father-child relationship and adequate parental mediation approach, such as active mediation, may contribute to reduction of Internet addiction risk in adolescents, especially in primary school adolescents.